2020
DOI: 10.1111/apt.15698
|View full text |Cite
|
Sign up to set email alerts
|

The use of pancreatic enzyme replacement therapy in patients with a diagnosis of chronic pancreatitis and pancreatic cancer in the US is infrequent and inconsistent

Abstract: Background: Patients with chronic pancreatitis or pancreatic cancer commonly develop exocrine pancreatic insufficiency, and may not be adequately treated with pancreatic enzyme replacement therapy (PERT). Aims:To estimate the frequency of diagnostic testing for exocrine insufficiency, and appropriate use of PERT, in a commercially insured population in the US. Methods:We utilised a nationally representative administrative database representing 48.67 million individuals in over 80 US healthcare plans to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 46 publications
1
42
0
1
Order By: Relevance
“…While PERT has been shown to increase body weight, quality of life and survival in patients with Heterogeneity: Chi 2 = 1.10, df = 2 (P = 0.58); I 2 = 0% Test for overall effect: Z = 3.49 (P = 0.0005) Heterogeneity: Tau 2 = 1.70, Chi 2 = 2.53, df = 1 (P = 0.11); I 2 = 60% Test for overall effect: Z = 1.41 (P = 0.16) PC, 13,14,29 its use is not widespread. Forsmark et al 35 noticed that only 21.9% of PC patients received PERT and that prescription was adequate in only 5.5%. Similar findings were reported in a study on APC patients from Australia in which only 21% of patients with malabsorption were prescribed PERT.…”
Section: Discussionmentioning
confidence: 99%
“…While PERT has been shown to increase body weight, quality of life and survival in patients with Heterogeneity: Chi 2 = 1.10, df = 2 (P = 0.58); I 2 = 0% Test for overall effect: Z = 3.49 (P = 0.0005) Heterogeneity: Tau 2 = 1.70, Chi 2 = 2.53, df = 1 (P = 0.11); I 2 = 60% Test for overall effect: Z = 1.41 (P = 0.16) PC, 13,14,29 its use is not widespread. Forsmark et al 35 noticed that only 21.9% of PC patients received PERT and that prescription was adequate in only 5.5%. Similar findings were reported in a study on APC patients from Australia in which only 21% of patients with malabsorption were prescribed PERT.…”
Section: Discussionmentioning
confidence: 99%
“…This study 9 emphasises that EPI is not investigated in most PC and CP patients. Furthermore, only a minority of patients received adequate PERT, which can improve outcomes.…”
Section: Chronic Pancreatitis (N = 37 061) Pancreatic Cancer (N mentioning
confidence: 96%
“…Forsmark et al 9 assessed the use and dosing of PERT in insured US patients with CP or PC from a national administrative database of over 48 million individuals between 2001 and 2013. At least one CP claim was made for 37,061 individuals.…”
Section: Chronic Pancreatitis (N = 37 061) Pancreatic Cancer (N mentioning
confidence: 99%
“…Several European studies have reported that many patients receive far less PERT or do not receive PERT at all [69,70]. Recently a retrospective study covering over 80 U.S. healthcare patients showed that only one in five patients with PDAC was prescribed PERT, whereas a minimally effective PERT dosage was prescribed in less than 10% [71].…”
Section: Pancreatic Enzyme Replacementmentioning
confidence: 99%